1998
DOI: 10.1046/j.1365-2141.1998.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron status in pregnant women: which measurements are valid?

Abstract: Anaemia in pregnancy in developing countries continues to be a public health problem of significant proportion. At least 50% of the anaemia has been blamed on iron deficiency. In populations where chronic inflammation and iron deficiency anaemia coexist, the criteria to accurately define iron status are not always clear. Similarly, in pregnancy, with marked physiological changes, cut-off points for biochemical parameters need to be re-examined. In this study we examined the diagnostic accuracy of iron paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
1
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(132 citation statements)
references
References 36 publications
0
124
1
7
Order By: Relevance
“…Others have found that among anemic as well as among nonanemic pregnancies, sTfR values are not influenced by iron stores [82,124]. Thus, elevated sTfR levels in late third trimester may help identify iron-deficient erythropoiesis with satisfactory specificity but low sensitivity, but reduced erythropoiesis limits the possibility of detecting iron deficiency in the rest of pregnancy [123,128,129].…”
Section: Soluble Tfr: a Marker Of Iron Status And/or Erythropoiesis?mentioning
confidence: 99%
“…Others have found that among anemic as well as among nonanemic pregnancies, sTfR values are not influenced by iron stores [82,124]. Thus, elevated sTfR levels in late third trimester may help identify iron-deficient erythropoiesis with satisfactory specificity but low sensitivity, but reduced erythropoiesis limits the possibility of detecting iron deficiency in the rest of pregnancy [123,128,129].…”
Section: Soluble Tfr: a Marker Of Iron Status And/or Erythropoiesis?mentioning
confidence: 99%
“…In NPNL individuals a serum ferritin of < 15-16 mg/l identifies the absence of stainable bone marrow with 75 % sensitivity and 98% specificity (60,61) . Only one study has carried out similar assessments of pregnant women (62) . In this study the most accurate cut-off point in late pregnancy was determined to be 30 mg/l, which is markedly higher than that found in NPNL women.…”
Section: Assessment Of Maternal Body Iron Storesmentioning
confidence: 99%
“…It is therefore most useful at the initial booking appointment since it can identify preexisting micronutrient deficiency that can be treated in time to prevent further deterioration (14)(15)(16) . During late pregnancy, however, it may fail to detect individuals with recently-developed deficiency brought about by the high demand for micronutrients (17,18) .…”
Section: Mean Corpuscular Volume: the Multi-purpose Screening Toolmentioning
confidence: 99%
“…14,[16][17][18][19] Recentemente, tem sido proposta a utilização da medida de receptores de transferrina como parâme-tro para detecção da deficiência de ferro, mesmo na Os citados receptores encontram-se aumentados na deficiência de ferro, nas anemias hemolíticas autoimunes e β-talassemias; e apresentam-se reduzidos em anemias aplásicas. 4,20,26 Estudos apontam uma boa sensibilidade desses receptores, 1,7,20,26,28 tendo sido demonstrada uma boa correlação entre eles com outros parâmetros, como CTLF, FeS e FS. 20 Skikne et al 26 (1990) sugeriram a utilização da relação receptores de transferrina/ferrina sérica ao invés dos dois parâmetros isoladamente, uma vez que, na deficiência de ferro a concentração da FS encontrase reduzida e a dos receptores de transferrina aumentada.…”
Section: Diagnóstico Do Estado Nutricional De Ferrounclassified
“…Os achados mostram que a concentração de receptores de transferrina, ao contrário dos outros parâmetros, não é afetada pela gestação nem por processos infecciosos e inflamatórios. 4,8,28 Flowers et al 13 (1989) observaram, em indivíduos normais, uma média de valores de receptores de transferrina de 5,6 mg/L, com uma variação entre 2 mg/L, 8 mg/L e 8,5 mg/L. Os níveis médios em indiví-duos com anemia falciforme e anemia por deficiência de ferro foi de 33 mg/L e 18 mg/L, respectivamente.…”
Section: Diagnóstico Do Estado Nutricional De Ferrounclassified